Methods and Processes for First Nations Health Curriculum Development for Nursing, Medicine, Dentistry and Allied Health Entry-Level Programs: A Scoping Review ... - Godwin, Shirley; Hyett, Nerida; McMahon, Mishel; McKinstry, Carol; Long, Natasha; Whiteside, Mary; Bruce, Chris (SAGE Journals, 2023)
The inclusion of First Nations health curricula in programs is critical for the development of culturally safe graduates, however, less is known about how to embed content into curriculum in ways that reflect best practice and pedagogy. The aim of this scoping review was to describe methods and processes of First Nations health curriculum development in nursing, medical, dentistry, and allied health entry-level programs in international peer-reviewed journals. Systematic searches of databases were completed including CINAHL, Proquest, Medline, and Informit; with additional searches in Google Scholar and First Nations-led journals. A total of 104 articles met inclusion criteria; the majority relating to medicine ( n = 38) and nursing/midwifery ( n = 17) student cohorts. Methods and processes for embedding First Nations health content are described, including First Nations-led development and co-leadership, resulting in a suggested model for curriculum development. Evidence-informed curriculum development is ...